Prevalence of Leaving against Medical Advice (LAMA) from Paediatric Wards Patients of Al-Tibri Medical College and Hospital (Medical Forum Monthly, 2021)
Objective: The aim of this study was to present the prevalent rate of LAMA among paediatric hospitalized patients.Study Design: Retrospective observational studyPlace and Duration of Study: This study was conducted at the Paediatric wards of Al-Tibri Medical College and Hospital, data was collected during 1 year from June 2018 to May 2019.Materials and Methods: Both genders, from infants till 12 year olds, admitted ICU / NICU and ward paediatric patients were included. SPSS was used for analysis of data. Frequency and percentages were reported for qualitative variables and Chi-Square test was applied to test for significance.Results: Total of 734 patients 107 (15%) patients Left Against Medical Advice among which 54 (50.5%) were males and most of them 74 (69.2%) being infants. Over half of the patients, i.e. A significant difference was reported in between type of discharge with age, month of admission and diagnosis.Conclusion: Our study reported a 15 % prevalence of LAMA among paediatric population reported in various other studies from both developing as well as developed countries. The prevalence rate was in between the rates presented in researches. Effective communicating techniques, awareness of health care system and improving health care performance are needed to minimise the rates of LAMA among patients.